The Relationship of Ethics and Interests: A Philosophical Study of Political Law and Economics: Hubungan Etika dan Kepentingan: Sebuah Studi Filsafat Hukum Politik dan Ekonomi - Yunus, Nur Rohim; Abdurrahman, Abdurrahman; Setiawan, Refly (Yapilin Press, 2025)
This article discusses the complex relationship between ethics and interests in political economic law. This relationship becomes increasingly relevant in the contemporary context, where public policy is often influenced by political and economic interests that dominate over moral or ethical considerations. This study aims to analyze the dynamics of the meeting and conflict between ethical values and interests in political economic law, and to examine how ethics should guide public policy and institutions, especially in terms of justice and social welfare. This study uses a qualitative method with a literature and legal study approach, analysing classical philosophical works and related legal and ethical theories. Through this approach, the author identifies challenges arising from the tension between personal or group interests and moral demands that should be the basis for policy making. The results of this study indicate that the role of philosophy is vital in maintaining the integrity of values in legal practice and economic policy, and criticise the technocratic approach that often ignores moral considerations. This study concludes that to create fair and sustainable policies, ethics must be the primary basis in every decision-making process in political and economic law.